Parallel computational fluid dynamics practice and theory : proceedings of the Parallel CFD 2001 Conference, Egmond aan Zee, the Netherlands (May 21-23, 2001) - Parallel CFD Conference (2001 : Egmond aan Zee, Netherlands); Wilders, P. (Amsterdam ; London : Elsevier, 2002)
ParCFD 2001, the thirteenth international conference on Parallel Computational Fluid Dynamics took place in Egmond aan Zee, the Netherlands, from May 21-23, 2001. The specialized, high-level ParCFD conferences are organized yearly on traveling locations all over the world. A strong back-up is given by the central organization located in the USA <SURL>http://www.parcfd.org</SURL>. These proceedings of ParCFD 2001 represent 70% of the oral lectures presented at the meeting. All published papers were subjected to a refereeing process, which resulted in a uniformly high quality. The papers cover not only the traditional areas of the ParCFD conferences, e.g. numerical schemes and algorithms, tools and environments, interdisciplinary topics, industrial applications, but, following local interests, also environmental and medical issues. These proceedings present an up-to-date overview of the state of the art in parallel computational fluid dynamics.
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Supercomputers -- Congresses; Electronic books